2018
DOI: 10.1177/0887302x18782778
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical and Comfort Properties of Sustainable Blended Fabrics of Bamboo With Cotton and Regenerated Fibers

Abstract: The worldwide growing need of cotton but its lower production has boosted the production of regenerated cellulosic fibers. This work compares the thermal comfort and mechanical properties of bamboo rayon fiber blends with cotton and other regenerated fibers. So, bamboo rayon fibers were blended with cotton, tencel lyocell, modal rayon, and viscose rayon. One-hundred-percent pure fabrics of bamboo rayon, cotton, tencel lyocell, modal rayon, and viscose rayon were made. Also, 50:50 blends of bamboo rayon with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Moreover, the plain-woven bamboo-cotton fabric in a 50:50 ratio demonstrated improved thermal conductivity and heat retention properties [116]. This study corroborated the work of Basit et al [117]. Furthermore, it has been shown that there is no remarkable distinction between cellulose acetate derived from traditional wood pulp and that derived from bamboo plants, indicating that bamboo has the potential to replace wood pulp for cellulose-derived fibrous materials, thereby mitigating deforestation and enabling forest sustainability [118].…”
Section: Bamboo In Textilessupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the plain-woven bamboo-cotton fabric in a 50:50 ratio demonstrated improved thermal conductivity and heat retention properties [116]. This study corroborated the work of Basit et al [117]. Furthermore, it has been shown that there is no remarkable distinction between cellulose acetate derived from traditional wood pulp and that derived from bamboo plants, indicating that bamboo has the potential to replace wood pulp for cellulose-derived fibrous materials, thereby mitigating deforestation and enabling forest sustainability [118].…”
Section: Bamboo In Textilessupporting
confidence: 90%
“…Moreover, the plain-woven bamboo-cotton fabric in a 50:50 ratio demonstrated improved thermal conductivity and heat retention properties [116]. This study corroborated the work of Basit et al [117].…”
Section: Bamboo In Textilessupporting
confidence: 89%
“…Retailer of fabrics sold one of the fabrics as bamboo/spandex blend. Wardingsih and Troynikov [11] used the term bamboo fabrics in their study and Basit, et al [32] tested 100% bamboo fibers as well as 50%/50% blend of bamboo/ rayon as blends of cotton, modal rayon, Tencel and viscose rayon.…”
Section: Discussionmentioning
confidence: 99%
“…polyester for its moisture management for next to skin apparel in another study [13]. They recommended finer yarns for inner layer (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and coarser yarns for the outer layer (29)(30)(31)(32)(33). Hussain, Nazir and Masood reported that double knit jersey structure (Outer and inner surfaces are made from different fibers) has better water transporting ability than rib knit fabrics that also have double structure [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, they can directly absorb perspiration from users into the fiber molecules, leaving no residual sweat on the skin, and preventing the growth of bacteria and the discomfort rendered by moisture and heat. Similarly, Tencel ® fibers also have unique advantages when applied to livelihood supplies, sanitary articles, industrial cloth, medical bandages, and adult/infant diapers, featuring a broad range of applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%